Innovative technologies in the system of physical education and sports - Safin. D. A (Zien Journals, 2025)
The article describes the importance of innovative technologies in the system of physical education and sports, their essence and relevance in modern times and their influence on the development of physical education and sports.
Keywords: technologies; physical education; sports